Modelling gas and dust around carbon stars in the Large Magellanic Cloud. Issue Volume 14:Issue S343(2019) (August 2018) - Srinivasan, Sundar; Chen, I.-K.; Scicluna, P.; Cami, J.; Kemper, F.
Abstract: In order to investigate the effect of dust production on the molecular absorption, we model the dust continuum and the 7.5 and 13.7 μ m acetylene absorption features in the Spitzer IRS spectra of 148 carbon stars in the Large Magellanic Cloud (LMC). Our preliminary investigation does not find a strong correlation between the dust-production rate and the column density of acetylene for the LMC sample. However, we will construct more models at high optical depths and probe a larger range of dust properties for more robust results.